Ureteropelvic Junction Obstruction and Parathyroid Adenoma: Coincidence or Link?. (17th October 2017) - Termos, Salah; AlKabbani, Majd; Ulinski, Tim; Sanjad, Sami; Kotobi, Henri; Chalard, Francois; Aoun, Bilal
Abstract : Congenital ureteropelvic junction obstruction (UPJO) is the most common cause of upper urinary tract obstruction in children. It is generally diagnosed in the routine work-up during antenatal period and is characterized by spontaneous recovery. It can be associated with urolithiasis; hence further investigation should be carried out. We report the case of a 15-year-old boy, who is known to have right UPJO, presented with right renal colic and discovered to have bilateral kidney stones. Further studies showed primary hyperparathyroidism and genetic analysis revealed a CDC73 mutation (initially HRPT2). We believe that association of UPJO and PHPT is a rare coincidence that can be linked. Careful work-up of children with UPJO and urolithiasis is recommended to exclude an underlying metabolic disease. Surgical correction can be evitable as treatment of the primary cause can lead to complete dissolution of kidney stones and improvement of the medical condition.